2019
DOI: 10.1021/acs.langmuir.8b04281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sample Loss Caused by Competitive Adsorption of Proteins in Vials Using Sodium Dodecyl Sulfate–Polyacrylamide Gel Electrophoresis

Abstract: Sample loss caused by competitive protein adsorption on solid surfaces from complex samples remains to be a major hurdle in sensitive analyses of proteins. No label-free techniques can easily quantify individual proteins adsorbed on irregular surfaces of Eppendorf vials or Falcon tubes, which are commonly used to contain complex biological samples. Multiplexed characterization of such adsorption by different proteins is technically challenging. Herein, we developed a direct protein analysis based on sodium dod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…We combined the lab‐scale recirculation experiment with a rinse‐stripping protocol adapted from Lee et al (2011) and Ranade et al (2019). Before each experiment (10 total), the cRPP was cleaned in an ultrasonic bath and then rinsed extensively with Milli‐Q water.…”
Section: Methodsmentioning
confidence: 99%
“…We combined the lab‐scale recirculation experiment with a rinse‐stripping protocol adapted from Lee et al (2011) and Ranade et al (2019). Before each experiment (10 total), the cRPP was cleaned in an ultrasonic bath and then rinsed extensively with Milli‐Q water.…”
Section: Methodsmentioning
confidence: 99%
“…We used a published trypsin digestion protocol [33,34] and monitored digestion efficiency overnight and at 24 and 48 h. The SDS-PAGE gel results of CHO cell lysate digestion at 24 and 48 h are shown in Figure 2. No obvious difference was observed among all the time points chosen.…”
Section: Trypsin Digestionmentioning
confidence: 99%
“…Control Chinese hamster ovary (CHO) cells were maintained in sterile F12 (Ham's) nutrient medium, pH 7.4 (Life Technologies, Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 10% FBS (Life Technologies) and maintained in a humidified environment at 37 • C with 5% CO 2 (Symphony 5.3A, VWR, Radnor, PA, USA) until 90% confluency. The CHO cells were transiently cotransfected with human cDNA encoding the Nav1.5 α-subunit, the β1-subunit, and eGFP following the PolyFect (Qiagen, Germantown, MD, USA) transfection protocol [33]. Transfected cells were grown in filtered sterile F12 (Ham's) nutrient medium, pH 7.4 (Life Technologies, Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 5% FBS and maintained in a humidified environment at 37 • C with 5% CO 2 [46].…”
Section: Cell Culture and Harvestingmentioning
confidence: 99%
“…A recent 2019 publication by Ranade et al . commented on the use of stripping agents to remove tightly adhered milk proteins from sample vials, particularly polypropylene vials 6 . Interestingly, they found that the metal chelator EDTA enhanced the surface adsorption of milk proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy proved very effective for a 27‐residue commercial peptide called Vn96 but was ineffective for the quantitative analysis of the intact proteins apomyoglobin and carbonic anhydrase. Our final strategy combined the use of low‐bind vials with the addition of an active‐site blocking agent or adsorption competitor 6 . In this case, we used the intact protein carbonic anhydrase at a concentration of 10 µg/mL as a blocker for apomyoglobin and the polypeptide ubiquitin at a concentration of 10 µg/mL as a blocker for carbonic anhydrase.…”
Section: Introductionmentioning
confidence: 99%